Cu-Chelated polydopamine nanoparticles as a photothermal medium and "immunogenic cell death" inducer for combined tumor therapy. Issue 16 (29th March 2022) - Xu, Na; Hu, Ao; Pu, Ximing; Wang, Juan; Liao, Xiaoming; Huang, Zhongbing; Yin, Guangfu
Abstract : A Cu(ii )-Chelated polydopamine nano-system (Cu–PDA) acts as photothermal agent (PTA), Fenton-like reaction initiator and "immunogenic cell death" inducer to mediate PTT/CDT synergistical tumor therapy and antitumor immune activation. Abstract : Chemodynamic therapy (CDT) and photothermal therapy (PTT) have been powerful technologies for tumor ablation. However, how to realize efficient CDT and PTT synergetic tumor ablation through a safe and intelligent system, remains a topic of great research value. Herein, a novel Cu-chelated polydopamine nano-system (Cu–PDA) with surface PEGylation and folate (FA) targeting modification (Cu–PDA–FA) was presented as a photothermal agent (PTA), Fenton-like reaction initiator and "immunogenic cell death" inducer to mediate PTT/CDT synergistical tumor therapy and antitumor immune activation. Primarily, the prepared Cu–PDA NPs possessed elevated photothermal conversion efficiency (46.84%) under the near-infrared (NIR) irradiation, bringing about hyperthermic death of tumor cells. Secondly, Cu–PDA catalyzed the generation of toxic hydroxyl radicals (˙OH) in response to the specific tumor microenvironment (TME) with the depletion of GSH, killing tumor cells with high specificity. Interestingly, the increase in local tumor temperature caused by PTT availed the production of ˙OH, and then the produced toxic ˙OH further led the tumor cells to be more sensitive to heat via impeding the expression of heat shock protein, so the synergistically enhanced PTT/CDT in tumor therapy could be achieved. Most importantly, the synergistical PTT/CDT could cause tumor cell death in an immunogenic way to generate in situ tumor vaccine-like functions, which were able to trigger a systemic antitumor immune response, preventing recurrence and metastasis without any other adjuvant supplementation. Overall, these Cu–PDA NPs will provide inspiration for the construction of a versatile nanoplatform for tumor therapy.